Pengaruh Beban Kerja dan Kompensasi terhadap Turnover Intention pada Karyawan Cafe Sapa Seduh - Tiara Puspa Laksitasadewi; Didin Kurniayu; Bangun Putra Prasetya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The high rate of employee turnover in the café business, along with café Sapa Seduh's record-high turnover of 40% in the past year, prompted the research. The study used a quantitative methodology with an explanatory focus. With complete sampling as the method of selection, the population comprised all eighteen permanent employees. A validated and reliable Likert-scale questionnaire was used to gather data. Multiple linear regression in SPSS version 26 was used to analyse the data. The findings indicated that there was a significant partial effect of the workload variable on turnover intention (significance value 0.000 < 0.05), but no significant partial effect of the compensation variable (significance value 0.481 > 0.05). Nevertheless, the combination of workload and compensation had a notable impact on turnover intention (significance value 0.000 < 0.05), as determined by an Adjusted R Square value of 0.851. These results show that employees' intention to leave is most affected by workload. Consequently, in order to lower turnover rates, management should prioritise the equitable management of staff workloads.